Pengaruh Social Media Instagram Marketing dan Brand Image terhadap Purchase Intention Produk Avoskin dimediasi oleh Brand Trust - Nadia Utami; Nonik Kusuma Ningrum; Agus Dwi Cahya (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The presence of beauty trends has a significant influence on the growth of the cosmetics and beauty industry in Indonesia. With the existence of the trends, consumer needs for skin care products have increased. So that makes many new brands present in the world of beauty in Indonesia, both local brands and brands from abroad. The presence of foreign brands makes competition between producers even higher. With this competition requires local brands to determine the right marketing strategy. Social media is one of the most appropriate marketing or promotional tools because it is easily accessible so that it can improve brand image and brand trust. This study aims to determine the effect of Social Media Marketing and Brand Image on Purchase Intention mediated by Brand Trust. The sample in this study were followers of Avoskin's Instagram account and lived in the city of Yogyakarta. Primary data was obtained from a questionnaire of 100 respondents with a technique with 100 respondents with purposive sampling technique. After that the data was analyzed using multiple linear regression analysis with purpose sampling, hypothesis testing using partial test (t) and sobel test using the SPSS ver. 25 program. The results showed that social media marketing variables had a positive and significant effect on brand trust, brand image had a positive and significant effect on brand trust, brand trust had a positive and significant effect on purchase intention, social media marketing had a positive and significant effect on purchase intention, and brand image variables had a positive and significant effect on purchase intention.